Establishing energy requirements for body weight maintenance: validation of an intake-balance method - Heymsfield, Steven B. (BMC Res Notes, 2017)
BACKGROUND: Experimentally establishing a group’s body weight maintenance energy requirement is an important component of metabolism research. At present, the reference approach for measuring the metabolizable energy intake (MEI) from foods required for body weight maintenance in non-confined subjects is the doubly-labeled water (DLW)–total energy expenditure (TEE) method. In the current study, we evaluated an energy-intake weight balance method as an alternative to DLW that is more flexible and practical to apply in some settings. METHODS: The hypothesis was tested that MEI from foods observed in a group of subjects maintaining a constant energy intake while keeping their weight within ±1 kg over 10 days is non-significantly different from DLW-measured TEE (TEE(DLW)). Six non-obese subjects evaluated as part of an earlier study completed the inpatient protocol that included a 3-day initial adjustment period. RESULTS: The group body weight coefficient of variation (X ± SD) during the 10-day balance period was 0.38 ± 0.10% and the slope of the regression line for body weight versus protocol day was non-significant at 1.8 g/day (R(2), 0.002, p = 0.98). MEI from foods observed during the 10-day balance period (2390 ± 543 kcal/day) was non-significantly different (p = 0.96) from TEE measured by DLW (2373 ± 713 kcal/day); the MEI/TEE(DLW) ratio was 1.03 ± 0.15 (range 0.87–1.27) and the correlation between MEI from foods and TEE(DLW) was highly significant (R(2), 0.88, p = 0.005). CONCLUSIONS: A carefully managed 10-day protocol that includes a constant MEI level from foods with weight stability (±1 kg) will provide a group’s body weight maintenance energy requirement similar to that obtained with DLW. This approach opens the possibility of conducting affordable weight balance studies, shorter in duration than those previously reported, that are needed to answer a wide range of questions in clinical nutrition. Trial registration The study is registered at http://www.clinicaltrials.gov (NCT01672632; August 20, 2012). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-017-2546-4) contains supplementary material, which is available to authorized users.